Penghindaran Penghindaran Pajak, Leverage dan Nilai Perusahaan: Dimoderasi oleh Transparansi - Pratami, Yolanda; Munashiroh, Hidayatul (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2024)
The objective of this research is to acquire empirical evidence regarding the impact of transparency on the relationship between tax avoidance and leverage in relation to a firm's value. Firm value is pivotal as it mirrors a company's performance, thereby influencing investors' perceptions. This study adopts a quantitative approach, utilizing EViews as an analytical tool to test a hypothetical model. The research specifically examines manufacturing firms listed on the Indonesia Stock Exchange during the period from 2020 to 2022. A purposive sampling technique was employed, yielding a sample size of 93 companies out of a population of 243. The empirical findings of this study indicate that tax avoidance practices can influence a company's value, whereas leverage does not. Additionally, transparency does not enhance the relationship between tax avoidance and leverage concerning firm value.